Feasibility of cardiovascular risk and sleep health screening in the transport industry. (September 2020) - Howard, Mark E.; Wolkow, Alexander P.; Wilkinson, Vanessa; Swann, Philip; Jordan, Amy S.; O'Donoghue, Fergal J.; Pierce, Robert J.; Hare, David L.
Abstract: Introduction: Motor vehicle crashes (MVCs) and cardiovascular disease account for the majority of workplace fatalities in the transport industry. This study evaluates the feasibility of a health education and screening program for commercial drivers in the transport industry, assesses its impact on workplace injuries, and determines risk factors for MVCs. Methods: Australian commercial drivers (N = 3873) were educated on, and assessed for sleep disorders, cardiovascular risk factors, and self-reported MVCs and driving hours. Recommendations were provided to follow-up medical conditions, if required. In a subsample, injury rates 12-months before and after the program were evaluated. The health program was conducted between 2003 and 2005. Data was accessed in 2011, and statistical analysis completed between 2011 and 2018. Results: Almost half (48.67%, 95% CI = 45.48–51.86) of participants were referred for follow-up, with 59% (56.77–61.23) attending follow-up. Ten percent had hypertension (10.07%, 8.50–11.64), 25.89% (23.14–28.63) had high-risk of obstructive sleep apnoea (OSA) and 13.99% (12.47–15.51) had excessive sleepiness. MVC risk increased in drivers self-reporting a fear of falling asleep while driving (AOR = 2.32, CI = 1.37–3.93), sleepiness (AOR = 2.42, CI = 1.58–3.70) and short sleep (AOR = 1.74, CI = 1.10–2.74). Extended driving hours were associated with obesity (OR = 1.006, CI = 1.002–1.010) and hypertension (OR = 1.009, CI = 1.003–1.015). A 17% reduction in workplace injuries was observed post-program participation. Conclusions: Cardiovascular risk factors and OSA were prevalent in drivers. Sleepiness was common and increased MVC risk, while extended driving hours were associated with an elevated cardiovascular risk profile. Compliance with medical follow-up was modest, but the reduced injury rates post-participation highlights the positive impact of health education and screening in this high-risk population. Highlights: 48.67% of commercial drivers were referred for medical follow-up after screening. Sleep problems were common, and increased the risk of motor vehicle crashes. Longer driving or work hours were associated with hypertension and obesity. A 17% reduction in workplace injuries was observed post-program participation. Transport companies should consider workplace sleep and cardiovascular screening.